Lysozyme Improves the Inhibitory Effects of Panax notoginseng Saponins on Phenotype Transformation of Vascular Smooth Muscle Cells by Binding to Ginsenoside Re - Huang, Yun; Cui, Lijian; Yang, Hongchao; Chen, Ning; Guo, Huishan; Gan, Xiaoruo; Wang, Rong; Shi, Weiye; Wu, Yu; Zhang, Yan; Lv, Pin (Frontiers in Nutrition, 2021)
Panax notoginseng saponins (PNS) have been used to treat cardiovascular diseases for hundreds of years in China. Lysozyme can bind to exogenous compounds and promote their activity. Nevertheless, knowledge of whether there is a synergistic role between lysozyme and PNS is far from sufficient. In this study, we show that the mixture of PNS and lysozyme synergistically inhibited platelet derived growth factor BB (PDGF-BB)-induced vascular smooth muscle cell (VSMC) viability, and in the five main components of PNS, GS-Re, but not GS-Rb1, NG-R1, GS-Rg1, or GS-Rd, reduced VSMC viability by combined application with lysozyme. Next, the supramolecular complexes formed by GS-Re and lysozyme were detected by mass spectrometry, and the binding ability increased with the concentration ratio of GS-Re to lysozyme from 4:1 to 12:1. In the supramolecular complexes, the relative contents of α-helix of lysozyme were increased, which was beneficial for stabilizing the structure of lysozyme. The 12:1 mixture of GS-Re and lysozyme (12.8 μmol/L GS-Re+1.067 μmol/L lysozyme) repressed PDGF-BB-induced VSMC viability, proliferation, and migration, which were associated with the upregulated differentiated markers and downregulated dedifferentiated markers. Finally, in CaCl2-induced rodent abdominal aortic aneurysm (AAA) models, we found that the 12:1 mixture of GS-Re and lysozyme slowed down AAA progression and reversed phenotype transformation of VSMCs. Thus, Gs-Re combined with a small amount of lysozyme may provide a novel therapeutic strategy for vascular remodeling-associated cardiovascular diseases.